Justice environnementale et développement des capabilités des jeunes du secondaire en contexte d'éducation à l'environnement et au développement durable (EEDD) - Christophe Ndong Angoué
This article examines the different perspectives on the concept of capabilities in normative economics and education. It also highlights the different challenges of its operationalization in the framework of the EIEDD-ANR-16-FRQSC project. By considering injustice as an inequality of the capabilities of individuals, the concept of capabilities offers the possibility to better question the idea of ​​environmental justice and modes of governance of environmental risks. In addition, by emphasizing individuals' freedom of choice and their freedom of agency, the Capability Approach provides a rich and nuanced perspective on the real freedoms of high school students and their power to act in matters of ecocitizenship.